SUPPLY CHAIN AND VALUE-ADDED ANALYSIS OF LAHAT COFFEE ON COFFEE SHOP IN PALEMBANG CITY - Afriyani Afriyani; Muhammad Yazid; Desi Aryani (Faculty of Animal and Agricultural Science, Diponegoro University, 2021)
Lahat is one of the Robusta coffee production centers in South Sumatra. The coffee beansproduced by this district are often used as raw material in the coffee shop in Palembang because of thedistinctive taste and aroma that coffee lovers love. Coffee shops opens new opportunities for Robustacoffee farming. This study aims to analyze the flow of the supply chain and the added value of Lahatcoffee beans used by coffee shop. This research was conducted through a survey of four coffee shops inPalembang. The results showed that there are two supply chain lines, (1) coffee farmers - collectors -retailers - market traders - consumers; (2) coffee farmers - processors - coffee shops - consumers. Thesecond pattern is better and more profitable than the first pattern because the quality of the coffeeproduced is higher. The average added value obtained from processing one kilogram of coffee cherriesinto ground coffee is Rp. 158,132.94, coffee bean into green bean is Rp. 427,798.55, and green beaninto a cup of coffee is Rp. 1,029,269.00. This value indicates that processing the coffee cherries intopowder and processing the selected coffee cherries in coffee shop are profitable.